Hope and Deception in Conception Bay: Merchant-Settler Relations in Newfoundland 1785-1855 - Bumsted, J. M. (Labour / Le Travail, 1996)
The article reviews the book "Hope and Deception in Conception Bay: Merchant-Settler Relations in Newfoundland 1785-1855," by Sean T. Cadigan.
Keywords: BOOKS – Reviews; BUSINESSPEOPLE; CADIGAN; Sean T.; HOPE & Deception in Conception Bay: Merchant-Settler Relations in Newfoundland 1785-1855 (Book); Nonfiction

1919: The Winnipeg General Strike Reconsidered - Bumsted, J. M. (The Beaver, 1994)
The year 1994 marks the seventy-fifth anniversary of the Winnipeg General Strike, one of the best-known events in modern Canadian history. It also marks the seventy-fifth anniversary of the composition of a lengthy history of the strike from the strikers' perspective which was first published in 1920... Much of the subsequent historical writing about the strike has treated this complex event along the lines first developed in the strikers' own history. The result has been the emergence of a monolithic and somewhat one-dimensional view of the strike. The account which follows examines in detail only a few of the more important components of this fascinating event. It attempts to introduce some multiple perspectives and perhaps to raise some new questions. –Introduction